Research on Tooth Flank Twist Based on Orthogonal Polynomials Characterization - Baoya Zhao; Bo Yu; Zhaoyao Shi; Yanqiang Sun; Guoqing Wu (Machines, 2022)
Tooth flank twist is a common phenomenon in the helical crowning modification of helical cylindrical gear, which reduces the performance of the gear. At present, the measurement of tooth flank twist is still in the stage of replacing surface with line. The development of 3-D measurement technology makes the acquisition of gear information more comprehensive and complete. By processing the 3-D point cloud data, the twist deviation on the tooth flank can be found, which is particularly important for improving the quality of the tooth flank. In this paper, a characterization method of tooth flank twist based on orthogonal polynomials was proposed, which can effectively separate the twist deviations existing on the tooth flank. The correctness of the method was verified by measurement experiments. Taking worm grinding wheel grinding to process helical crowning modification as an example, the model of various parameters of the gear and the amount of twist was established and the twist deviation in processing was predicted. This provides a new method for eliminating the twist deviation of the tooth flank.